Cultural Values Transformation of Momosad in the Management of Wetland Rice Fields in the Buffer Zoneof Bolaang-MongondowNational Park - Meity Melani Mokoginta; Dewa Oka Suparwata (Jurnal Ilmu Pertanian Indonesia, 2026)
Momosad is a gotong royong activity in which a group of farmers work together to maintain their land. Currently, Momosad is transitioning from a labor-based to a wage-based Momosad (commercial). The research aims are (1) to uncover Momosad's cultural values, which are still relevant today, (2) to describe the elements that influence changes in the values in land management, and (3) to examine patterns of changes in the values. This study employed a qualitative technique using the Miles and Huberman Model, involving interviews, observations, and documentation. Data was processed using the triangulation rule. The results suggest that there are three types of Momosad agricultural production activities in Dumoga. (1) Pure-Momosad has family values; (2) Semi-Momosad values unity and dependence. (3) Non-Momosad (commercial) values include agreement and dependency. There are three variables that influence Momosad's change: (1) pre-colonial, (2) colonial, (3) development, and (4) regional autonomy. Cultural contact, development period, and regional autonomy all have a significant impact on the pattern of change in the value. The pattern of change began with cultural contact between transmigration and local residents, evolved into the power to form villages during Momosad construction, and the autonomy of the region became a political commodity used to rally the masses. Keywords: cultural values, Momosad, transformation